2020
DOI: 10.1164/rccm.202003-0512st
|View full text |Cite
|
Sign up to set email alerts
|

Making Medical Treatment Decisions for Unrepresented Patients in the ICU. An Official American Thoracic Society/American Geriatrics Society Policy Statement

Abstract: Background and Rationale: ICU clinicians regularly care for patients who lack capacity, an applicable advance directive, and an available surrogate decision-maker. Although there is no consensus on terminology, we refer to these patients as "unrepresented." There is considerable controversy about how to make treatment decisions for these patients, and there is significant variability in both law and clinical practice. Purpose and Objectives: This multisociety statement provides clinicians and hospital administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 68 publications
0
26
0
2
Order By: Relevance
“…Patients, surrogates, and clinicians consistently rate ACP as important, especially by those who have experienced decision‐making for serious illness 2‐5 . In addition, ACP research has seen sustained growth (Figure 1), and prominent organizations have called for its implementation and reimbursement 6‐11 . Recent ACP studies have shown an overall benefit for patient, surrogate, and clinician outcomes; however, some results have been mixed, 12 leading some to question the utility of ACP 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients, surrogates, and clinicians consistently rate ACP as important, especially by those who have experienced decision‐making for serious illness 2‐5 . In addition, ACP research has seen sustained growth (Figure 1), and prominent organizations have called for its implementation and reimbursement 6‐11 . Recent ACP studies have shown an overall benefit for patient, surrogate, and clinician outcomes; however, some results have been mixed, 12 leading some to question the utility of ACP 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The Journal recently published a joint statement of the American Thoracic Society and the American Geriatrics Society on medical decision-making for unrepresented patients in the critical care setting ( 1 ). This statement is an important contribution, but it neglects at least one significant aspect of the decision-making process for unrepresented patients, as follows: how to identify the point in an unrepresented patient’s treatment course at which an alternative decision-making process should be implemented.…”
mentioning
confidence: 99%
“…Similarly, this policy statement omits certain fine-grained details, noting that its six recommendations must be “tailored to the capabilities of the individual institution” and that “institutions should have flexibility” in how they implement the guidance. Indeed, at the heart of this policy statement is an explicit tradeoff between “excessive and insufficient procedural safeguards” ( 1 ). Although this policy statement sets some broad parameters, it is appropriate that various institutions will strike the balance between fairness and feasibility differently.…”
mentioning
confidence: 99%
“…Second, whether a decision concerns major medical treatment or life-sustaining treatment, the decision-making process should promote the same five ethical goals ( 1 ). At least for the subset of consent-requiring procedures that involve significant risk, institutions should approximate the decision-making process that the policy statement provides for life-sustaining treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation